3D cell culture models: Drug pharmacokinetics, safety assessment, and regulatory consideration. Issue 5 (16th June 2021) - Wang, Hongbing; Brown, Paul C.; Chow, Edwin C.Y.; Ewart, Lorna; Ferguson, Stephen S.; Fitzpatrick, Suzanne; Freedman, Benjamin S.; Guo, Grace L.; Hedrich, William; Heyward, Scott; Hickman, James; Isoherranen, Nina; et al.
Abstract: Nonclinical testing has served as a foundation for evaluating potential risks and effectiveness of investigational new drugs in humans. However, the current two‐dimensional (2D) in vitro cell culture systems cannot accurately depict and simulate the rich environment and complex processes observed in vivo, whereas animal studies present significant drawbacks with inherited species‐specific differences and low throughput for increased demands. To improve the nonclinical prediction of drug safety and efficacy, researchers continue to develop novel models to evaluate and promote the use of improved cell‐ and organ‐based assays for more accurate representation of human susceptibility to drug response. Among others, the three‐dimensional (3D) cell culture models present physiologically relevant cellular microenvironment and offer great promise for assessing drug disposition and pharmacokinetics (PKs) that influence drug safety and efficacy from an early stage of drug development. Currently, there are numerous different types of 3D culture systems, from simple spheroids to more complicated organoids and organs‐on‐chips, and from single‐cell type static 3D models to cell co‐culture 3D models equipped with microfluidic flow control as well as hybrid 3D systems that combine 2D culture with biomedical microelectromechanical systems. This article reviews the current application and challenges of 3D culture systems in drug PKs, safety, and efficacy assessment, and provides a focused discussion and regulatory perspectives on the liver‐, intestine‐, kidney‐, and neuron‐based 3D cellular models.